A study to find the impact of customer purchasing on traditional shopping V/S online shopping (International Journal of Food and Nutritional Sciences, 2022)
: In recent years, the rise of e-commerce has revolutionized the way consumers make purchasing decisions, with customer reviews play a crucial role in shaping those decisions. Online shopping has become increasingly popular due to the convenience and accessibility it provides, and customer reviews have become a valuable resource for online shoppers in making informed decisions. On the other hand, traditional shopping still holds a significant place in the market, and customer reviews still play a vital role in the purchasing decisions of customers in physical stores